Peran Public Relations dalam Komunikasi Antar Budaya Sekolah Internasional: Mountainview Christian School - Elizabeth Setyati (JIKA (Jurnal Ilmu Komunikasi Andalan), 2024)
Quality of education is a crucial foundation for enhancing human resources (HR), especially in an era of globalization that demands strong intercultural competence and social adaptation. International schools like Mountainview Christian School (MCS) play an important role in developing superior HR within a multicultural environment. This study aims to analyze the role of Public Relations (PR) at MCS in managing intercultural communication, both internally and externally. This research employs a qualitative method with a descriptive ethnographic approach. Data were collected through interviews, observations, and documentation. The results indicate that Public Relations (PR) practitioners at Mountainview Christian School (MCS) perform four primary roles: as expert advisors by formulating policies to address disparities between national and expatriate staff; as problem-solving process facilitators by organizing activities that respond to cultural differences; as communication technicians who professionally utilize digital communication media; and as communication facilitators ensuring the smooth flow of information. These PR roles are supported by the intercultural communication conditions at MCS, which accommodate the concept of sociocultural adjustment, focusing on empathy, cultural interconnectedness, and efforts to reduce tensions in intercultural interactions, thus fostering inclusive and effective communication within a multicultural environment. Pendidikan berkualitas merupakan fondasi penting dalam upaya meningkatkan sumber daya manusia (SDM), terutama di era globalisasi yang menuntut kompetensi antar budaya dan adaptasi sosial yang kuat. Sekolah internasional seperti Mountainview Christian School (MCS) berperan penting dalam membentuk SDM unggul di lingkungan multikultural. Penelitian ini bertujuan menganalisis peran Public Relations (PR) di MCS dalam mengelola komunikasi antar budaya, baik dari aspek internal maupun eksternal, menggunakan metode kualitatif dengan pendekatan etnografi deskriptif. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa praktisi Public Relations (PR) di Mountainview Christian School (MCS) menjalankan empat peran utama, yaitu sebagai penasihat ahli dengan membuat kebijakan untuk mengatasi kesenjangan antara staf nasional dan staf ekspatriat, fasilitator proses pemecahan masalah dengan menyelenggarakan kegiatan yang merespons perbedaan kultural, teknisi komunikasi yang memanfaatkan media komunikasi digital secara profesional, serta fasilitator komunikasi dalam memastikan kelancaran arus informasi. Peran PR ini didukung oleh kondisi komunikasi antar budaya di MCS yang mengakomodasi konsep sociocultural adjustment, dengan fokus pada empati, keterkaitan budaya, serta upaya mengurangi ketegangan dalam interaksi antar budaya, sehingga tercipta komunikasi yang inklusif dan efektif di lingkungan yang multikultural.